THE IMPORTANCE OF DISMENOREA HANDLING EFFORTS IN ADOLESCENT NOT PRESENT AT SCHOOL - Cathy Jessica M. Wolff; Indriani Yauri (Jurnal Ilmiah Perawat Manado (Juiperdo), 2018)
Background: Dysmenorrhea is stiffness or spasms in the lower abdomen that occur before, during, or during menstruation, which can interfere with daily activities. When pain arises various kinds of treatment efforts will be done by some women either using drugs or without drugs. Experiencing dysmenorrhoea for women certainly can be detrimental and can cause discomfort when going to do daily activities, especially in young women who are generally a student. With good handling efforts by young women will certainly reduce the absence rate at school. Aims : of this study was to determine the relationship between efforts to manage dysmenorrhoea in adolescent girls with absence from school. Method: The research design used was descriptive quantitative using a cross sectional approach. The research sample using purposive sampling techniques amounted to 50 respondents. Data analysis uses chi-square test. Results : of the analysis obtained a value of 0.001 for non-pharmacological efforts by young women towards absence from school and 0.030 for pharmacological efforts by young women towards absence from school with significance value α <0.05, which means there is a significant relationship between efforts to manage dysmenorrhoea in adolescent girls with absence attend school. Conclusion: This research can be used as a reference material for parents, medical personnel especially that it is very important for young women to know about dysmenorrhoea as well as handling efforts that need to be done. And it is recommended to health workers and the school to take part in providing counseling about dysmenorrhoea and its treatment efforts. For further research in order to see things that can be investigated that have not been listed in this study. An example is the socioeconomic factor, and attitude.